CBR system for identifying traditional Chinese herbs / Chan Ho Sang - Chan , Ho Sang (2003)
This project documentation is an exercise submitted to the Faculty Computer Science and Information Technology, University of Malaya as a first stage report for the final year project WXES3181 which in turn serves as a partial fulfillment for the Bachelor of Computer Science degree. This project aims to demonstrate the feasibility of the application of the Case-Based Reasoning (CBR) method in identifying traditional Chinese herbs for certain illness or diseases. CBR has been proposed for tasks in which past experiences are exploited and adapted to solve the current problems. Art enterprise is the CBR development tool used in the beginning, the system will be introduced and its objectives will be defined together with the project schedule. The following chapter will present some explanations and background of AI and CBR technologies; traditional Chinese herbs and development tools used in implementing the system. Then, the methodologies will be discussed and reasons for the choice of case-based reasoning techniques are explained. The development tools and system requirements are also outlined. Finally, the result of system design will be presented in the final chapter of the proposal. The data flow diagram and user interface design were outline in this chapter too.